2017
DOI: 10.1017/s0960258517000113
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of different compounds in smoke derived from legumes and grasses acting on seed germination and seedling emergence

Abstract: Our previous study showed that smoke derived from alfalfa (Medicago sativa) caused different germination responses compared with that from prairie hay (Festuca hallii) and wheat straw (Triticum aestivum), but the mechanism remained unclear. In this study, we used Salad Bowl lettuce (Lactuca sativa) as a quick bioassay to trace the active compounds in each of these three smoke solutions. Column chromatography and high performance liquid chromatography (HPLC) were used to separate and identify active fractions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(77 reference statements)
3
5
0
Order By: Relevance
“…The current study clearly shows that plant-derived smoke-water treatments, particularly the smoke-water derived from white willow (SW 1 ) and lemon eucalyptus (SW 5 ), effectively improved GP, GR, and seedling growth of the tested crops. In accordance with our results, previous studies have shown that smoke-water and smoke-derived compounds have a positive effect on seed germination and the post-germination parameters of crops such as wheat [47], onion [48], tomato [49], okra [50], papaya [51], and lettuce [14,27]. Additionally, our results provide evidence that smoke-water can actively break dormancy in gladiolus [52].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current study clearly shows that plant-derived smoke-water treatments, particularly the smoke-water derived from white willow (SW 1 ) and lemon eucalyptus (SW 5 ), effectively improved GP, GR, and seedling growth of the tested crops. In accordance with our results, previous studies have shown that smoke-water and smoke-derived compounds have a positive effect on seed germination and the post-germination parameters of crops such as wheat [47], onion [48], tomato [49], okra [50], papaya [51], and lettuce [14,27]. Additionally, our results provide evidence that smoke-water can actively break dormancy in gladiolus [52].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, there is scientific debate about the effects of smoke-water and its active compounds (KARs) on germination parameters and whether smoke-water can substitute for light conditions or not. The germination percentage of some light sensitive crops such as lettuce seeds ( Lactuca sativa ) can be significantly increased under dark conditions by using smoke-water [6,27]. On the other hand, Nelson et al [28] showed that the effect of KAR on Arabidopsis seed germination was observed only under light conditions and not under dark conditions, which confirms the results found in tomato, gladiolus, and scotch marigold in the current study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations